2004
DOI: 10.1242/jcs.00978
|View full text |Cite
|
Sign up to set email alerts
|

Foxj1 regulates basal body anchoring to the cytoskeleton of ciliated pulmonary epithelial cells

Abstract: The forkhead box transcription factor Foxj1 is required for cilia formation and left-right axis determination. To define the role of Foxj1 in ciliogenesis, microarray analysis was performed to identify differentially expressed genes in the pulmonary epithelium of foxj1 +/+ and foxj1 -/-mice. In the absence of Foxj1, the expression of calpastatin, an inhibitor of the protease calpain, decreased. RNase protection confirmed the decrease in calpastatin expression and decreased calpastatin was detected in the proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
102
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 50 publications
8
102
0
Order By: Relevance
“…Studies of ciliogenesis in the quail oviduct showed that localization of basal bodies to the apical cell domain depends on actin dynamics 35 . In line with this, ciliogenesis is defective in Foxj1 mutant mice, due to abnormal basal body anchoring to the actin-based apical cytoskeleton, and failure of RhoA-mediated apical actin enrichment [44][45][46][47] . The hypothesis that PCP signaling regulates apical actin network formation required for docking of basal bodies and normal ciliogenesis predicts that mutations in other genes that control PCP in mice should similarly lead to cilia dysfunction and hydrocephalus.…”
mentioning
confidence: 67%
“…Studies of ciliogenesis in the quail oviduct showed that localization of basal bodies to the apical cell domain depends on actin dynamics 35 . In line with this, ciliogenesis is defective in Foxj1 mutant mice, due to abnormal basal body anchoring to the actin-based apical cytoskeleton, and failure of RhoA-mediated apical actin enrichment [44][45][46][47] . The hypothesis that PCP signaling regulates apical actin network formation required for docking of basal bodies and normal ciliogenesis predicts that mutations in other genes that control PCP in mice should similarly lead to cilia dysfunction and hydrocephalus.…”
mentioning
confidence: 67%
“…This mucociliary clearance protects the airway from infection. Forkhead box protein J1 (FOXJ1) is a transcription factor associated with the activation of genes necessary for the anchoring of basal bodies at the apical surface and initiating ciliogenesis (41,42). In our differentiation protocol, FOXJ1 gene expression is highly up-regulated after switching to ALI at day 17 following initiation of differentiation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence suggests that Foxj1 functions in airway cells during late stages of ciliogenesis and is not sufficient to drive cilia formation in nonciliated adult epithelial cells (27,28). Therefore, FOXJ1-GFP expression in cells without cilia most likely marks embryonic cells already committed to the ciliated lineage.…”
Section: Ciliated Cell Specification and Differentiation During Develmentioning
confidence: 99%
“…Both strains use a promoter region of FOXJ1, a gene that encodes a forkhead domain transcription factor required for late stages of ciliogenesis (27,28). Our analysis of FOXJ1-GFP embryonic lungs provides a unique overview of the appearance of ciliated cells during development.…”
mentioning
confidence: 99%